(untitled) (Journal of Social Sciences Review, 2025)
Worldwide, women are at higher risk of developing mental disorders than men. The available research from developing nations shows that women have more psychological and social vulnerabilities. Pakistan is a developing country with immense challenges for women, such as socio-economic disadvantages. There is a scarcity of research in Pakistan looking at the Socio-economic Status (SES) of young female students and their association with mental health issues. This research aimed to find out the association of SES with mental health problems among unmarried female students of Punjab, Pakistan. The study was based on a cross-sectional descriptive research design. The independent variables were the socioeconomic factors, and the dependent variable was poor mental health. The data and the assessment of psychological morbidity among the study population were collected using the General Health Questionnaire (GHQ-12) and a self-designed questionnaire. All the frequencies and percentages were computed using descriptive statistics, and a Chi-Square test was carried out to determine the relationship between dependent and independent variables. The study would be a significant addition for the identification of mental health risks among young women, which can be utilized by policy-makers and NGOs, particularly working for women’s empowerment. The study would also provide a knowledge base for future studies in this area.